Modeling factors related to earthquake preparedness: a structural equation modeling approach - Azadeh Fatehpanah; Elham Maraghi; Anthony Coetzer-Liversage; Mahmood Karimy; Amir H. Pakpour; Majed Maripour; Nematollah Jaafarzadeh Haghighi Fard; Marzieh Araban (BMC Public Health)
Abstract Introduction Global evidence suggests that natural disasters are on the rise, and that earthquake harm disproportionally impacts developing countries. To mitigate these harms, disaster preparedness is an important behavioral strategy in earthquake risk mitigation. However, there is limited evidence about the levels of preparedness in developing countries, especially Iran. Therefore, this study aimed to investigate earthquake preparedness among the general public, using the Theory of Planned Behavior (TPB) as a theoretical framework. Method This methodological study was conducted in Iran in 2022, involving 302 participants selected through stratified random sampling. Data was collected using a valid and reliable questionnaire. Structural equation modeling (SEM) was employed to analyze TPB constructs, including attitudes, subjective norms, perceived behavioral control, and intentions, in relation to earthquake preparedness behaviors. The statistical analyses encompassed descriptive statistics, t-tests, ANOVA, correlation coefficients, confirmatory factor analysis, and structural equation modeling. Results Results show that attitudes toward disaster preparedness, subjective norms, and perceived behavioral control significantly (< 0.05) influenced residents’ disaster preparedness intentions. Additionally, there was good model fit of the TPB in explaining earthquake preparedness behavior. For confirmatory factor analysis (CFA) of TPB model the fit indices were CMin/df = 1.35 (< 3), RMSEA = 0.03 (< 0.05); CFI = 0.96 (> 0.95); TLI = 0.95 (= 0.95), and for SEM model they were CMin/df = 1.36 (< 3), RMSEA = 0.03 (< 0.05); CFI = 0.96 (> 0.95); TLI = 0.96 (> 0.95). Conclusion The overall fit indexes were acceptable indicating the TPB model is a valid and reliable measurement model for screening population-level readiness for earthquake preparedness, developing and/or implementing health promotion interventions. The findings also suggest that disaster education programs should emphasize the importance of attitudes, subjective norms, and perceived behavioral control in promoting disaster preparedness.